Trial of Insulin for Poststroke Hyperglycemia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
The effect of glucose potassium insulin (GKI) infusion (compared to saline as control) within 24 hours of ischemic stroke was studied in patients (> 18 years old) with blood glucose >126mg/dl (7mmol/l) admitted to Southern General Hospital, Glasgow, Scotland.